1977
DOI: 10.1104/pp.60.6.877
|View full text |Cite
|
Sign up to set email alerts
|

Light versus Dark Carbon Metabolism in Cherry Tomato Fruits

Abstract: Previous studies (6, 7) have shown that high PEP' carboxylase activities are found in green tomato fruit tissues; this finding was subsequently confirmed (12). More recently, we demonstrated that the incubation of tomato tissues with "4C-bicarbonate in the light results in the incorporation of radioactivity into malate and RPPC compounds (8). The external pericarp of thE fruit, the flesh, contains a relatively high RuDP carboxylase activity and exhibits a large incorporation of "4CO2 into RPPC compounds. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…These results indicate that the modified PEPCK level directly affects the sugar and organic acid contents, likely through gluconeogenesis. While it has been reported that the predominant metabolic flow in the flesh of tomato and grape is glycolysis (Carrari et al 2006;Famiani et al 2014), early labelling studies demonstrated that gluconeogenesis occurs during tomato fruit ripening (Farineau and Laval-Martin 1977;Halinska and Frenkel 1991). Our present results indicate that gluconeogenesis is involved in sugar accumulation in fruit, and PEPCK plays a regulatory role in this process.…”
Section: Discussionsupporting
confidence: 59%
“…These results indicate that the modified PEPCK level directly affects the sugar and organic acid contents, likely through gluconeogenesis. While it has been reported that the predominant metabolic flow in the flesh of tomato and grape is glycolysis (Carrari et al 2006;Famiani et al 2014), early labelling studies demonstrated that gluconeogenesis occurs during tomato fruit ripening (Farineau and Laval-Martin 1977;Halinska and Frenkel 1991). Our present results indicate that gluconeogenesis is involved in sugar accumulation in fruit, and PEPCK plays a regulatory role in this process.…”
Section: Discussionsupporting
confidence: 59%
“…Bahrami et al (2001) isolated the gene from tomato and showed that its expression increases during ripening. Although previous labeling studies have demonstrated that gluconeogenesis occurs in ripening tomato fruit (Farineau and Laval-Martin, 1977;Halinska and Frenkel, 1991), and cold-inducible PEPCK was reported in rapeseed (Sáez-Vásquez et al, 1995), its regulation in response to abiotic stress is not fully understood in plants. Our data suggest that salinity stress enhances gluconeogenesis, as well as metabolic flow in ripe fruit, resulting in high-Brix fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from radiolabeling work in tomato fruit (Farineau, 1977;Halinska and Frenkel, 1991) suggested that gluconeogenesis does occur during ripening stages, when sugars are accumulating rapidly. Here, we observed that when cytosolic PEPCK was reduced (PEPCK lines), this led to reduced levels of the major sugars, Glc and Fru, during fruit ripening, accompanied by an accumulation of malate, which provides further evidence for gluconeogenesis from organic acids (Halinska and Frenkel, 1991) and the important role of PEPCK enzymes in this process.…”
Section: Effects Of Cytosolic Pepck and Plastidic Nadp-me On Starch Bmentioning
confidence: 99%
“…This has led to the suggestion that PEPCK is involved in this dissimilation and that part of this dissimilated malate may be used in gluconeogenesis (Leegood and Walker, 2003;Famiani et al, 2005Famiani et al, , 2009. In contrast, NADP-ME isoforms function in chloroplasts and the cytosol (Drincovich et al, 2001;Gerrard Wheeler et al, 2005) and catalyze the reversible conversion of malate and pyruvate (Farineau, 1977;Drincovich et al, 2001). In tomato, NADP-ME has been implicated in respiration during ripening, providing pyruvate and/or NADPH as a substrate for respiration (Farineau, 1977;Edwards and Andreo, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation